Desain primer secara in silico dan optimasi PCR untuk deteksi gen penyandi ovary ecdysteroidogenic hormone (OEH) pada nyamuk Aedes aegypti yang terinfeksi Wolbachia: In silico primer design and PCR optimization for detection of the gene encoding ovary ecdysteroidogenic hormone (OEH) in Aedes aegypti mosquitoes infected with Wolbachia - Septiasari, Ni Putu Senshi; Dwijastuti, Ni Made Sri; Handayani, Nyoman Sri; Darmayanti, Putu Diah (Perhimpunan Entomologi Indonesia, 2025)
Female Aedes aegypti (Linnaeus) mosquitoes bearing Wolbachia are reported to have behavioral changes during mating and blood-sucking. The ovary ecdysteroidogenic hormone (OEH) is a hormone released when female mosquitoes consume blood so that it influencing egg formation. Initial studies regarding the genetics of the A. aegypti mosquito carrying Wolbachia are very necessary to able to do this help control dengue vectors. The polymerase chain reaction (PCR) method is an appropriate method for genetic studies. Primer design is an initial and crucial stage in genetic studies because designing specific primers will determine the success of the PCR process. This research includes several stages of in silico primer design to design OEH gene primers and test the optimization of the in vitro designed primers. The in silico stage which involves primer design, primer BLAST, primer quality testing, and in silico PCR simulations. The designed primers were tested in vitro by performing PCR using various variations in primer concentration (0.2 µM and 0.4 µM) and annealing temperature (start from 45 oC to 60 oC). The results obtained in silico were two pairs of primers: primers OEH 8 and OEH 9. The results of the in silico test obtained a DNA product size of 264 bp for Primer OEH 8 and 236 bp for primer OEH 9, and the PCR efficiency was 95%. The results of the in vitro test showed only primer OEH 9 met the primer criteria according to the in silico test: primer concentration of 0.4 µM with an annealing temperature of 57 oC.